1982
DOI: 10.1007/bf03007528
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus as a possible sign of subclinical muscular dystrophy predisposing to rhabdomyolysis and myoglobinuria: a study of an affected family

Abstract: Administration of succinylcholine to normal individuals results in alterations in muscle membrane integrity expressed as a slight increase in the concentrations of creatine phosphokinase (CK) in serum and appearance of small amounts of myoglobin in the urine, but without clinical symptoms. Subjects with strabismus due to congenital muscular dystrophy may develop more significant rhabdomyolysis expressed as muscle stiffness and weakness, massive myoglobinuria, marked elevation of serum CK and other enzymes, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Three of the six patients who developed renal failure had clues to muscle disease, namely preoperative elevation of creatinine kinase, 10 history of painful swelling of the thighs 6 and family history of Duchenne muscular dystrophy.9 Subclinical muscle disease possibly predisposing to rhabdomyolysis should be suspected in patients with squints or scoliosis. 21 The relationship of malignant hyperpyrexia to suxamethonium-induced rhabdomyolysis is unclear. It has been suggested that this condition is a 'forme fruste' of malignant hyperpyrexia, in which rhabdomyolysis also occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the six patients who developed renal failure had clues to muscle disease, namely preoperative elevation of creatinine kinase, 10 history of painful swelling of the thighs 6 and family history of Duchenne muscular dystrophy.9 Subclinical muscle disease possibly predisposing to rhabdomyolysis should be suspected in patients with squints or scoliosis. 21 The relationship of malignant hyperpyrexia to suxamethonium-induced rhabdomyolysis is unclear. It has been suggested that this condition is a 'forme fruste' of malignant hyperpyrexia, in which rhabdomyolysis also occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Even leaving aside the controversial issue of the reported high percentage of biopsies positive for MH after MMS, the clinical literature contains many case reports of fulminant MH, sometimes leading to death, if inhalation anesthetic agents are continued after MMS (4)(5)(6)(7)(8). In at least four of the patients presented by Littleford et al, dantrolene was used and the anesthetic stopped.…”
Section: A Methods For Withholding Sedatives From Patients Before Obtamentioning
confidence: 99%
“…Suxamethonium is known to release potassium from cells, increase serum CPK concentrations (Tammisto and Airaksinen, 1966) and cause myoglobinuria (MacLaren, 1968) in normal patients, including children. Halothane potentiates the enzyme-releasing effects of suxamethonium, but may also produce this result to a lesser degree when administered as a sole agent to normal patients (Lewandowski, 1982). The potassium-and enzyme-releasing effects are potentiated in patients with Duchenne's PMD and in patients with subclinical myopathy, as demonstrated by increased resting CPK and lactic dehydrogenase (LD) concentrations in serum (Lewandowski, 1981).…”
Section: Anaesthetic Considerationsmentioning
confidence: 99%
“…Halothane potentiates the enzyme-releasing effects of suxamethonium, but may also produce this result to a lesser degree when administered as a sole agent to normal patients (Lewandowski, 1982). The potassium-and enzyme-releasing effects are potentiated in patients with Duchenne's PMD and in patients with subclinical myopathy, as demonstrated by increased resting CPK and lactic dehydrogenase (LD) concentrations in serum (Lewandowski, 1981). Lewandowski (1982) described a boy with normal resting serum CPK concentration and increased serum LD concentrations who developed rhabdomyolysis, myoglobinuria, acidosis, tachycardia and hyperpyrexia following halothane and suxamethonium.…”
Section: Anaesthetic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation